2009
DOI: 10.1063/1.3117239
|View full text |Cite
|
Sign up to set email alerts
|

Photoreflectance study of the energy gap and spin-orbit splitting in InNAs alloys

Abstract: Photoreflectance spectroscopy has been applied to study the energy gap and the spin-orbit splitting in InNAs alloys with the nitrogen concentration changing from 0% to 0.88%. It has been observed that the energy gap of InNAs decreases with the increase in nitrogen concentration (about 60 meV per 1% of nitrogen) but the spin-orbit splitting almost does not change. It shows that nitrogen atoms in InNAs alloys influence mainly the conduction band, i.e., shift this band toward the valence band. The bowing paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…This result indicates that the bowing parameter decreases with increasing Bi content. Similar results are found in GaAsN and InAsN alloys [38,39]. The composition dependence of the bowing parameter are due to the large differences between the sizes of the alloyed As and Bi atoms and between their atomic orbital energies, spatially separated and sharply localized band edge states are formed in the alloy.…”
Section: Resultssupporting
confidence: 84%
“…This result indicates that the bowing parameter decreases with increasing Bi content. Similar results are found in GaAsN and InAsN alloys [38,39]. The composition dependence of the bowing parameter are due to the large differences between the sizes of the alloyed As and Bi atoms and between their atomic orbital energies, spatially separated and sharply localized band edge states are formed in the alloy.…”
Section: Resultssupporting
confidence: 84%
“…12,13 High quality samples with nitrogen compositions up to 2.5% were obtained, with intense low-temperature PL emission and relatively strong room-temperature ͑RT͒ PL emission at a wave-length of 4.5 m. Photoreflectance ͑PR͒ studies on similar epilayers allowed probing the dependence on N content of both the band gap and the spin-orbit splitting of InAsN up to a N concentration of 0.88%. 18 It was concluded that only the conduction states are affected by N, in agreement with the results obtained in the Ga͑In͒AsN alloy system and fully consistent within the framework of the band-anticrossing ͑BAC͒ model. 19 In the present work we use a series of structural and optical characterization techniques to study InAs 1−x N x epilayers grown by molecular beam epitaxy ͑MBE͒ on InAs substrates.…”
Section: Introductionsupporting
confidence: 76%
“…As a consequence, the BAC parameters for InAsN are usually determined with low accuracy. Recently, Zhuang et al 12 performed PL studies on InAsN/InAs samples similar to those studied in this work, and obtained a value of C MN = 2.5 eV at 4 K and a value of C MN = 2.7 eV at 300 K. Kudrawiec et al 18 reported PR spectra of similar samples with N contents up to ϳ1% and obtained C MN = 2.7 eV at 20 K. Previous studies obtained much lower C MN values ͑Veal et al 11 found a value of C MN = 1.77 eV with PL at 80 K; Shih et al 9 and Kuroda et al 6 performed absorption measurements at 300 K and obtained C MN = 1.68 eV and 1.86 eV, respectively, after correcting for the Burstein-Moss effect͒. Vurgaftman and Meyer 31 give a recommended value of 2.0 eV.…”
Section: Pl and Optical Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Because of this feature III-V-N alloys (so-called dilute nitrides) are very promising candidates for various optoelectronic applications including solar cells and GaAs-based telecommunication laser diodes. 2,[5][6][7] Unfortunately the incorporation of nitrogen also deteriorates the optical quality of the III-Vs by inducing carrier localization at low temperatures and strong nonradiative recombination at room temperature.…”
Section: Introductionmentioning
confidence: 99%